Research on the Guidance Mechanism for the Price Signal of Power Grid Connection Service - Jia Jingzi; Zeng Ming (E3S Web of Conferences, 2023)
At present, the utilization hours of thermal power continue to decline, and renewable energy generation also has a serious socket phenomenon, so it is necessary to guide the construction of power side selection points through price signals, so as to promote the smooth integration of more power generation into the grid. This study focuses on the connection services provided by grid enterprises to power side and demand side, analyzes and summarizes the connection charging practices of different countries, designs a shallow connection cost recovery model according to energy strategy and the characteristics of supply and demand side in our country, and puts forward feasible suggestions for renewable energy generation connection charging, in order to promote the investment and construction of grid and the consumption of renewable energy.